Big data jurisdicional: o uso de inteligência artificial para apoiar soluções de casos judiciais no processo eletrônico e o problema da vulneração da privacidade e dos dados pessoais dos jurisdicionados. - Holanda, Irving William Chaves (2024)
This dissertation explores the fundamental aspects of technology related to the legal context, which requires a primary study on the disruptive evolution of procedural law with the adoption of the electronic process and a discussion about the creation of virtual legal assistants. Later, the instruction addresses the essential human rights that should guide the development of virtual justice. A short approach is made on the topic of digital inclusion, intending to distinguish between vulnerable groups and cyber-excluded individuals. In a third stage, this study focuses on the emergence of a theory of digital jurisdiction. The planned topics include the reformulation of the classic concept of jurisdiction, based on the deterritorialization of justice and an emphasis on the ubiquity paradigm. Examples of the use of artificial intelligence in the judicial field in different countries around the world are presented. In the fourth chapter, concepts related to jurisdictional big data are explored. An analysis is carried out on the application of blockchain technology to ensure security in processes managed by AI, the role of programming codes in the development of computational intelligence, as well as a focus on the integration of artificial intelligence in the management of jurisdictional big data. It is also discussed about the use of helpful technologies for the electronic process, such as Machine Learning, Deep Learning, Data Mining, Process Mining, jurimetrics and artificial neural networks (ANN). A glimpse into artificial superintelligence and the use of AI systems to improve information governance is provided. Finally, the study focuses on the sensitive issues of application of AI by the judge courts, when the challenge of data protection in the big data era is addressed. Concepts such as the Orwell effect and panopticism in the digital age are brought up, and it is highlighted the concern to guarantee the fundamental right to privacy of personal data. On this occasion, this work makes a punctual parallel with the Matrix movie, and also provides brief analysis on the application of the Brazilian General Data Protection Law (and the Brazilian National Council of Justice Resolutions, nos. 331/2020 and 363/2021) on the protection of data used by AI systems within the scope of the Judiciary. In conclusion, the study reveals the need to carry out audits on the jurisdictional big data bank, as well as addressing the issue of civil liability in cases of infringement of the right to privacy due to the use of artificial intelligence in procedural acts.